2010
DOI: 10.1111/j.1755-3768.2010.02040.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association study of age-related macular degeneration in the Spanish population

Abstract: Purpose To investigate new genetic risk factors and replicate reported associations with advanced age related macular degeneration (AMD) in a prospective case - control study developed with a Spanish cohort. Methods Three hundred and fifty-three unrelated patients with advanced AMD (225 with atrophic AMD, 57 with neovascular AMD, and 71 with mixed AMD) and 282 age-matched controls were included. Functional and tagging SNPs in 55 candidate genes were genotyped using the SNPlex™ genotyping system. Single SNP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 69 publications
(102 reference statements)
2
25
0
Order By: Relevance
“…PON1 has an equally broad infl uence on human health, having been linked to vascular disease, Parkinson's disease ( 57-59 ), systemic lupus erythematosus ( 60-62 ), breast cancer ( 63, 64 ), age-related macular degeneration (65)(66)(67)(68)(69)(70)(71), and diabetes ( 36, 37 ) among other disorders. A fuller understanding of the determinants of PON1 activity should include the effects of diet.…”
Section: Discussionmentioning
confidence: 99%
“…PON1 has an equally broad infl uence on human health, having been linked to vascular disease, Parkinson's disease ( 57-59 ), systemic lupus erythematosus ( 60-62 ), breast cancer ( 63, 64 ), age-related macular degeneration (65)(66)(67)(68)(69)(70)(71), and diabetes ( 36, 37 ) among other disorders. A fuller understanding of the determinants of PON1 activity should include the effects of diet.…”
Section: Discussionmentioning
confidence: 99%
“…ARMS2 gene polymorphism has been reported to be a significant AMD risk factor in the Spanish population (Brión et al, 2011). In addition, Cruz-González et al (2014) identified a significant association between rs10490923 and the risk of developing AMD among Spanish individuals.…”
Section: Discussionmentioning
confidence: 97%
“…We are currently applying the evidence base presented in Table 2 and Figure 1 to guide investigations designed to identify core elements of a "molecular phenotype" (a pattern gene regulation/expression and DNA variation) representing individual capacity to use transporters, receptors, enzymes, and hormones targeting or affected by MXs in ways that may reduce risk of AMD incidence or progression. Although we have not yet identified any single sequence variant explaining a proportion of variance in AMD risk comparable to those of the complement pathway genes, there is now informative work examining putative AMD-associated single-nucleotide polymorphisms present in genes encoding proteins involved in MX transport (121,131,137,146,(148)(149)(150)(151)(152)(153)(154)(156)(157)(158)(159)(160)(161), binding/capture (141,162,163), cleavage (158,160), and diseases associated with lower MX status (177)(178)(179)(180)(181)(182)(183)(184). Projects examining the associations of MX-related genes with retinal pathophysiology in in vivo models have supported inferences on AMD relations with variants in MX transport genes (128,130,136,143).…”
Section: The Promise Of Molecular Genetics For Examining the Effect Omentioning
confidence: 98%
“…[177][178][179][180][181][182][183][184] Numbers in parentheses correspond to reference numbers. Full names for genes represented by symbols are available from http://www.ncbi.nlm.nih.gov/gene.…”
mentioning
confidence: 99%